A preliminary in vitro study on the antimicrobial property of honey on streptococcus mutans - Sicat, Jannice V.
Honey, the world's oldest natural sweet, has played an important role as food sweetener and as ancient medicine in many cultures. Honey has been known as an effective remedy for burns, wounds, skin ulcers, cough, and other systemic diseases. But in recent studies, it has been discovered that honey has antimicrobial properties that can inhibit a broad spectrum of bacterial species. Aside from this, many reports show that honey has bactericidal, bacteriostatic, antifungal, anticariogenic, and anti-inflammatory activity. Therefore, the aim of the study was to evaluate in vitro the antimicrobial property of honey against Streptococcus mutans at different concentrations and time intervals. 5 ml_ of the inoculum were mixed in separate test tubes containing 25%, 50%, 75%, 100% honey concentrations, pure distilled water, ampicillin and saline solution. 2 ml_ of these solutions were transferred to test tube samples containing 3 ml_ TYC broth. The procedure was repeated every 15 minutes for 11/2 hours. The turbidity of the samples indicating the inhibition of growth of S. mutans was determined using spectrophotometer. The results of the study showed that only honey concentrations have significant difference, furthermore, 75% and higher concentrations were the most effective against S. mutans. The length of time is not statistically significant.